Translation Discourse 4.0: Variety of Formats, Genres and Trends - Elina Novikova; Anna Naumova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2021)
The article considers the specific character of modern translation discourse, trends and opportunities of realization in the era of changes and global challenges. The relevance of the article is determined by the need to establish common and distinctive forms of expression and formats of translation discourse. The representative sources of three communicatively active discursive practices constitute the empirical base of the paper: scientific / translation studies translation discourse; professional / industry translation discourse; didactic translation discourse. The textual material of the discourse under consideration is analyzed in order to identify thematic dominants of three subtypes under consideration. The similarities and differences of the topics discussed by the translation community within the framework of the selected discursive practices are determined. Sources of translation discourse in Russian and German linguistic cultures were also involved in the analysis to identify common and distinctive features. The analysis revealed the tendency of the Russian-language translation discourse to be a more profound scientific search and substantiation of translation problems, and, on the contrary, the tendency of the German- and English-language discourses to discuss applied issues. The analyzed subtypes of translation discourse reveal certain unifying features: current challenges reaction rapidity, new phenomena and trends in society. However, these subtypes have translation tools of their own, traditions and formats that shape thematic dominants of each direction of the discourse. Thus, the paper revealed the dynamic nature of the discourse, on the one hand, and its sustainable development, on the other.